Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780190499037.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Affect as a Potential Determinant of Physical Activity and Exercise

Abstract: The promotion of physical activity and exercise has been a persistently challenging problem for industrialized societies. Traditionally, these behaviors have been conceptualized as resulting from the rational processing of information (e.g., regarding anticipated benefits, personal capabilities, sources of support). Therefore, attempts to change these behaviors have relied on the provision of information. The persistent failure to account for substantial portions of behavioral variance or raise physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Given the dynamic nature of affective responses to exercise, it is advised that such responses are recorded throughout the entire exercise bout (ie, pre‐, during, and post‐exercise) . Such an approach ensures that the most influential affective elements of exercise are captured (ie, the peak affect , the end affect, and the slope of affective change during the bout) . Focusing on affective constructs when designing interventions to promote physical activity may hold promise, although it has been suggested that there is a paucity of information regarding how we can achieve this in practice …”
Section: Dual‐mode Theory Of Affective Responses To Exercisementioning
confidence: 99%
“…Given the dynamic nature of affective responses to exercise, it is advised that such responses are recorded throughout the entire exercise bout (ie, pre‐, during, and post‐exercise) . Such an approach ensures that the most influential affective elements of exercise are captured (ie, the peak affect , the end affect, and the slope of affective change during the bout) . Focusing on affective constructs when designing interventions to promote physical activity may hold promise, although it has been suggested that there is a paucity of information regarding how we can achieve this in practice …”
Section: Dual‐mode Theory Of Affective Responses To Exercisementioning
confidence: 99%
“…Moreover, exercise class attendance was measured quasi-objectively by weekly observation of attendance so that we can rule out systematic bias of subjective measures of PA (Jekauc et al, 2014). The fact that we measured affective states rather than affective attitudes, affective judgments or anticipated affective responses which are not affective states per se (Ekkekakis et al, 2018) is also one of the several merits of this study. If one assumes that affect is not a cognitive or reflective sensation (Russell, 2003), it is not necessary to measure it as a cognitive construct: By asking participants to reflect about their affective attitudes or judgments, however, the answer is the result of cognitive operations (Ekkekakis et al, 2018).…”
Section: Strength Limitations and Future Directionsmentioning
confidence: 99%
“…The fact that we measured affective states rather than affective attitudes, affective judgments or anticipated affective responses which are not affective states per se (Ekkekakis et al, 2018) is also one of the several merits of this study. If one assumes that affect is not a cognitive or reflective sensation (Russell, 2003), it is not necessary to measure it as a cognitive construct: By asking participants to reflect about their affective attitudes or judgments, however, the answer is the result of cognitive operations (Ekkekakis et al, 2018). Applying the Feeling Scale (Hardy and Rejeski, 1989) and Felt Arousal Scale (Svebak and Murgatroyd, 1985), we are coming closer to measuring affective states per se and thereby extend the literature on the role of affect.…”
Section: Strength Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of progress made towards increasing physical activity at the populationlevel has led researchers to question the efficacy of the 'rational education' approach, which has predicated public health campaigns for decades (Ekkekakis, Zenko, Ladwig, & Hartman, 2018). This approach assumes that individuals are rational and if provided with complete information pertaining to a behaviour, they are likely to change their behaviour in the desired manner (Ekkekakis, 2017).…”
Section: Statement Of Contributionmentioning
confidence: 99%